Tomatidine Extraction from Various Solvents and Cancer Inhibition Mechanism Through In Silico Analysis - Lisdiana, Lisdiana; Iswari, Retno Sri; Christijanti, Wulan; Harjono, Harjono; Sasi, Fitri Arum; Dafip, Muchamad (Trends in Sciences, 2023)
Tomatidine is an alkaloid-steroid contained in tomato plant organs that potentially developed as an anti-cancer molecule. However, inappropriate use of solvents is frequently becoming an obstacle in the extractions process. In addition, the mechanism of action of tomatidine in the inhibition of cancer cell signaling pathways needs to be investigated. Therefore, this research aims to discover an appropriate solvent to extract tomatidine effectively, and to analyze the inhibition mechanism of tomatidine against the cancer growth pathway. A total of 80 kg of fresh tomatoes were cut into pieces and steamed at 120 °C for 30 min, then mashed and soaked for 3 days in 70 % ethanol, aquadest, petroleum ether, and chloroform separately, continued with GC/MS analysis. Molecular docking was conducted using targeted proteins including B-Raf proto-oncogen serine/ threonine protein kinase (BRAF), Vascular endothelial growth factor A (VEGFA), Smoothened protein (SMO), Cyclin-dependent kinase 2 (CDK2), and Tyrosine-protein kinase/ Janus kinase-1 (JAK1). The ligand-receptor was performed using AutoDock Vina v1.2.0. The highest extracted tomatidine was found in chloroform at 2.44 % of total alkaloid-steroid, and cannot be found in water. The highest interaction is observed in the SMO-tomatidine interaction complex, followed by JAK-1. Furthermore, physicochemical properties of tomatidine make it invaginated into the hydrophobic side of the target proteins that are mainly triggered by van der Waals and alkyl interaction. Based on the in-silico study, tomatidine significantly interacted in the oncogenic signaling pathways that therapeutically potential inhibit cancer cell proliferation. Further study should be focused on the effectiveness analysis of the SHH signaling pathway in the cancer cell. HIGHLIGHTS Important findings in this study include: Tomatidine, an alkaloid-steroid, is properly extracted in chloroform, petroleum ether and 70 % ethanol, however cannot extracted in aquadest. Furthermore, the aquadest content in 70 % ethanol is likely to reduce the solubility of the tomatidine The tomatidine physicochemical property provides a closed covalent bond that makes it more insoluble in the polar solvent. The only polar side is supported by the hydroxyl group in C-4, side chain C-17, and amide side in N-24 that allowed hydrogen bond formation which is relevant to the docking result In molecular docking, tomatidine strongly triggers Van der Waal forces, alkyl, and pi interaction than hydrogen bond or ionic force Interestingly, ligand-receptor interaction always makes tomatidine invaginated or folded into the protein hydrophobic side and strongly attract non-polar and aromatic amino acid, mostly Val, Ala, Leu, and Phe The significant finding is that tomatidine creates valid interactions with CDK2, BRAF, VEGFA, JAK1, and SMO that are involved in cancer cell proliferation, evading apoptosis, and sustained angiogenesis. The highest interaction is observed in the SMO-tomatidine interaction complex, which may affect the Sonic Hedgehog (SHH) signaling pathway (one of the most significant oncogenic pathways in various types of cancer) Tomatidine is therapeutically potential to inhibit cancer cell proliferation through protein inhibition activities against the SHH signaling pathway in the cancer cell GRAPHICAL ABSTRACT